Influence of grazing technologies on the indices of chestnut soils in western Kazakhstan - Nasiyev, B. N.; Bekkaliyev, A.K.; Manolov, I.; Shibaikin, V. (Polish Journal of Soil Science, 2020)
Degradation of pastures caused by anthropogenic and climatic factors leads to desertification, loss of soil fertility, reduces productivity of the pasture grass and it is a prerequisite for socio-economic problems. Pastures of Western Kazakhstan cover more than 70% of the lands under economic use and are the main fodder source for the farm animals. In the late years, degradation of pastures in Western Kazakhstan takes place due to intensive animal grazing. The aim of research is to study the impact of technology for grazing the farm animals on the pastures soil cover to prevent the processes of degradation and desertification, as well as the rational use of pasture ecosystems. Through these studies, experimental data were obtained on the current state of the pastures soil cover in Western Kazakhstan with different types of chestnut soils depending on the grazing technology. An excess intensive grazing of the farm animals has negative influence on physical and chemical factors of the chestnut soil types. Деградация пастбищ, вызванная антропогенными и климатическими факторами, приводит к опустыниванию, потере плодородия почв, снижению продуктивности пастбищных трав и является предпосылкой для возникновения социально-экономических проблем. Пастбища Западного Казахстана занимают более 70% земель хозяйственного использования и являются основным источником корма для сельскохозяйственных животных. В последние годы деградация пастбищ в Западном Казахстане происходит из-за интенсивного выпаса животных. Целью исследования является изучение влияния технологии выпаса сельскохозяйственных животных на почвенный покров пастбищ для предотвращения процессов деградации и опустынивания, а также рационального использования пастбищных экосистем. Благодаря этим исследованиям были получены экспериментальные данные о современном состоянии почвенного покрова пастбищ Западного Казахстана с различными типами каштановых почв в зависимости от технологии выпаса. Чрезмерно интенсивный выпас сельскохозяйственных животных отрицательно сказывается на физических и химических факторах каштановых почв.
Keywords: импакт-фактор 2020; скопус; зарубежные авторы; научный журнал; дальнее зарубежье; периодическое издание; пастбища; деградация почвы; grazing; degradation; chestnut soils; technologies anthropogenic source; q 3; процентиль 26